Pretreatment anxious depression as a predictor of side effect frequency and severity in escitalopram and aripiprazole adjunctive therapy. Issue 5 (25th March 2022) - Espinola, Caroline W.; Khoo, Yuelee; Parmar, Roohie; Demchenko, Ilya; Frey, Benicio N.; Milev, Roumen V.; Ravindran, Arun V.; Parikh, Sagar V.; Ho, Keith; Rotzinger, Susan; Lou, Wendy; Lam, Raymond W.; et al.
Abstract: Objective: To report side effect frequency and severity in patients with major depressive disorder (MDD) receiving escitalopram and aripiprazole adjunctive therapy and to examine whether pretreatment anxious depression is associated with the number and presence of specific side effects. Methods: 188 of the 211 trial participants provided information on side effects during treatment with escitalopram (10–20 mg) for 8 weeks, and nonresponders received further augmentation on aripiprazole (2–10 mg) adjunctive therapy for another 8 weeks, whereas responders remained on escitalopram. Participants completed the Toronto Side Effects Scale at weeks 2, 4, 10, and 12. Covariate‐adjusted negative binomial regression and Wilcoxon tests examined the association between anxious depression (GAD‐7 ≥ 10) and number of side effects. Covariate‐adjusted logistic regression and chi‐square tests explored the association between anxious depression and specific side effects. Results: For both therapies, the most frequent side effects were also the most severe. They mostly related to the central nervous system (CNS) (i.e., drowsiness and nervousness). Between baseline and week 2, the number of side effects participants experienced (incidence rate ratio [IRR] = 1.38, p = .010) or had trouble with (IRR = 1.34, p = .026) was significantly higher among those with anxious depression for escitalopram but not adjunctive aripiprazole. Further, odds of experiencing and having trouble with nervousness and agitation were also significantly higher in anxious depression for escitalopram only ( p < .05). Conclusion: Patients on escitalopram and aripiprazole adjunctive therapy may experience and have trouble with CNS side effects. Pretreatment anxious depression may predispose escitalopram recipients with MDD to developing side effects, especially those related to anxiety. Abstract : This study demonstrates the utility of a standardized side effects questionnaire (TSES) and advances our understanding of the association between pretreatment anxious depression and an increased number of side effects. Patients with anxious depression have significantly more side effects in the first weeks of escitalopram therapy than patients with nonanxious depression, particularly those related to anxiety (i.e., nervousness, agitation).